Photographic and descriptive musculoskeletal atlas of chimpanzees : with notes on the attachments, variations, innervation, function and synonymy and weight of the muscles /: with notes on the attachments, variations, innervation, function and synonymy and weight of the muscles. ([2013]) - Unknown
No abstract available